2022
DOI: 10.3390/insects13090833
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoid Wasps Can Manipulate Host Trehalase to the Benefit of Their Offspring

Abstract: Trehalase is an essential hydrolase of trehalose in insects. However, whether and how trehalase performs in the association of parasitoid wasps and their hosts still remains unknown. Here, the exact function of trehalase of the general cutworm Spodoptera litura after it was parasitized by its predominant endoparasitoid Meterous pulchricornis was elucidated. Two trehalase genes (SlTre1, SlTre2) were identified, and they were highly expressed five days after parasitization by M. pulchricornis. Then, we successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This protein was also found to be highly expressed the venom gland of several species of parasitoids, indicating a role in the complex host manipulations performed by parasitoid wasp venom [56]. In the host-parasitoid system Spodoptera litura-Meterous pulchricornis, it has been reported that the parasitoid induces the expression of two trehalases to ensure a suitable nutritional environment for parasitoid development [57].…”
Section: Discussionmentioning
confidence: 95%
“…This protein was also found to be highly expressed the venom gland of several species of parasitoids, indicating a role in the complex host manipulations performed by parasitoid wasp venom [56]. In the host-parasitoid system Spodoptera litura-Meterous pulchricornis, it has been reported that the parasitoid induces the expression of two trehalases to ensure a suitable nutritional environment for parasitoid development [57].…”
Section: Discussionmentioning
confidence: 95%
“…We observed that the treatment group could induce a certain abdominal segment contraction in the larvae, similar to morphological abnormalities that did not lead to death in a short time of outer epidermal loss. Previous studies have revealed that parasitic wasps create a suitable nutritional environment for their offspring by upregulating the trehalase activity of host Spodoptera litura larvae, thereby positively affecting the normal pupation rate, emergence rate, adult proportion, and offspring size [48]. A decrease in the transcription and translation levels of TRE can downregulate the expression of CHT and CHS, leading to difficulties with molting and the abnormal development of insects that often results in death [49].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the VgR expression can cause Vg to be deposited in large amounts in the hemolymph. This prevents its smooth entry into the ovaries, ultimately hindering ovarian tube development and significantly reducing egg production [48,57]. The prevention of a normal egg output by blackened and clumped egg and mating sacs in the fallopian tubes may have been a major reason for the decrease in egg production.…”
Section: Discussionmentioning
confidence: 99%